1D/3D Heterogeneous Assembling Body as Trifunctional Electrocatalysts Enabling Zinc–Air Battery and Self‐Powered Overall Water Splitting. (10th October 2021) - Zhou, Guizhong; Liu, Guishan; Liu, Xiaobin; Yu, Qingping; Mao, Huimin; Xiao, Zhenyu; Wang, Lei
Abstract: Developing low‐cost, efficient, and stable trifunctional electrocatalyst for oxygen reduction reaction (ORR), oxygen evolution reaction (OER), and hydrogen evolution reaction (HER) is still a significant challenge. Herein, this study reports a zeolitic imidazolate framework (ZIF) derived trifunctional electrocatalyst, composed of Co5.47 N and Co7 Fe3 (CoFeN) that embedded into 1D N‐doped carbon nanotubes modified 3D cruciform carbon matrix (NCNTs//CCM). Benefiting from the robust interfacial conjugation of Co5.47 N/Co7 Fe3 and the 1D/3D hierarchical structure with a large surface area, the as‐prepared CoFeN‐NCNTs//CCM display trifunctional electrocatalytic activity for ORR (half‐wave potential of 0.84 V), OER (320 mV at 10 mA cm –2 ), and HER (−151 mV at 10 mA cm –2 ). The assembled Zn‐air battery exhibits high power density (145 mW cm –2 ), enhanced charge–discharge performance (voltage gap of 0.76 V at 10 mA cm –2 ), and long‐term cycling stability (over 445 h). The resultant overall water‐splitting cell achieves a current density of 10 mA cm –2 at 1.63 V, which can compete with the best reported trifunctional catalysts. What is more, the self‐assembled Zn‐air batteries are utilized to power the overall water splitting successfully, verifying great potential of the CoFeN‐NCNTs//CCM as functional material for sustainable energy storage and conversion system. Abstract : This study reports a zeolitic imidazolate framework derived from trifunctional electrocatalyst, which is composed of Co5.47 N and Co7 Fe3 (CoFeN) embedded into 1D N‐doped carbon nanotubes modified 3D cruciform carbon matrix (NCNTs//CCM). Benefiting from the robust interfacial conjugation of Co5.47 N/Co7 Fe3 and the 1D/3D hierarchical structure, the as‐prepared CoFeN‐NCNTs//CCM enable Zn‐air battery and self‐powered overall water splitting successfully.